INFLUENCE OF ULTRASONIC TREATMENT ON SHELF LIFE OF DRINKS BASED ON GRAIN RAW MATERIALS - Kazakov I.O.; Kiseleva T.F.; Eremina I.А.; Mikova D.S. (Техника и технология пищевых производств)
At present producers of soft drinks pay great attention to the development of products using natural ingre-dients. The purpose of the research was to study the influence of ultrasound on polygrain drink shelf life. It is re-vealed that such drinks have a rather short shelf life if not subjected to any treatment. The analysis of earlier pub-lished papers devoted to the influence of ultrasonic waves that possess a great amount of mechanical energy and cause a number of physical, chemical and biological phenomena has been performed. The influence of intensive ultrasonic radiation ranging from 45 to 90 W/cm2 and lasting for 2, 3, 5 minutes on the amount of microorganisms in a polygrain drink has been studied. The results of the conducted research showed that by the 6th day of the experiment the amount of microorganisms in the untreated drink was 6 times the amount in the initial sample. As for organoleptic characteristics, their worsening was observed, sour taste and smell, and turbidity being developed in the drink. It has been proved that ultrasonic treatment of the drink approximately two times increases its shelf life. It has also been established that 2 - 3 min treatment isn't sufficient to achieve the desired effect. The study has also shown that the increase in intensity of ultrasonic radiation decreases the amount of microorganisms. The 5 min treatment and the ultrasonic wave intensity of 90W/cm2 have been established to be the optimum mode. At this mode the quantity of microorganisms has decreased by 92 – 95% in comparison with the control sample. The technological scheme of polygrain drink production including the stage of ultrasonic treatment aiming at the increase of polygrain drink shelf life from 7 to 14 days has been developed.